PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP INTERNET FINANCIAL REPORTING PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Putu Diah Putri Idawati; I Gusti Ayu Ratih Permata Dewi (STIMI Handayani Denpasar, 2017)
This study aims to examine the effect of profitability and firm size on the disclosure of internet financial reporting companies in Indonesia, especially manufacturing companies. The data used are external secondary data in the form of financial statements and annual reports of manufacturing companies listed on the Indonesia Stock Exchange in 2016. Selection of samples by purposive sampling method and obtained 96 companies. Data analysis techniques used are logistic regression analysis. Test results show that profitability has a significant positive effect on IFR, while firm size has positive effect not significant to IFR. Basically IFR is influenced by how much sense of responsibility of a company in complying with the rules set by Bapepam- LK regarding the disclosure of information in particular and how big the responsibility of the company in providing information about the condition of the company to the public or parties with the interest of the company not how The size of the company.